Melanoma whole exome sequencing identifies (V600E)B-RAF amplification-mediated acquired B-RAF inhibitor resistance - Shi, Hubing (2012)
The development of acquired drug resistance hampers the long-term success of B-RAF inhibitor (B-RAFi) therapy for melanoma patients. Here we show (V600E)B-RAF copy number gain as a mechanism of acquired B-RAFi resistance in four out of twenty (20%) patients treated with B-RAFi. In cell lines, (V600E)B-RAF over-expression and knockdown conferred B-RAFi resistance and sensitivity, respectively. In (V600E)B-RAF amplification-driven (vs. mutant N-RAS-driven) B-RAFi resistance, ERK reactivation is saturable, with higher doses of vemurafenib down-regulating pERK and re-sensitizing melanoma cells to B-RAFi. These two mechanisms of ERK reactivation are sensitive to the MEK1/2 inhibitor AZD6244/selumetinib or its combination with the B-RAFi vemurafenib. In contrast to mutant N-RAS-mediated (V600E)B-RAF bypass, which is sensitive to C-RAF knockdown, (V600E)B-RAF amplification-mediated resistance functions largely independently of C-RAF. Thus, alternative clinical strategies may potentially overcome distinct modes of ERK reactivation underlying acquired B-RAFi resistance in melanoma.